A multi-parameter miniature photometric analyser for fully automated environmental water monitoring - Paesani, Daniele (Array, 2019)
Nowadays, the increasing demand for constant in-situ monitoring of clean water, wastewater and sea water requires the deployment of automated platforms capable of on-line autonomous sampling, extended unattended operation and of multi-analyte detection. The Micro Loop Injection Analyser (μLIA) system hereby presented relies on integrated additively manufactured opto-fluidic components which allow for increased performance solutions to be implemented cost-effectively and in miniaturised footprints, targeting a wide spectrum of applications which ranges from in-situ environmental monitoring and field water testing to industrial process analysis. Preliminary tests of the μLIA unit have shown good reproducibility and stability of the system and a good performance of its self-calibration routines.